Patients Have Poor Postoperative Recall of Information Provided the Day of Surgery but Report Satisfaction With and High Use of an E-mailed Postoperative Digital Media Package - Kyle Shultz, D.O; Marissa Mastrocola, M.D; Tyler Smith, D.O; Brian Busconi, M.D (Elsevier, 2023)
Purpose: To understand what portions of the surgical day patients remember, what parts of an e-mailed media package regarding their surgery patients are used, and how that information affects their surgical experience. Methods: Patients undergoing an outpatient arthroscopic procedure were approached in the preoperative area and asked to remember 3 words. Postoperatively, they were seen by the surgeon to discuss surgical findings and instructions. They were then e-mailed a multimedia package containing a thank you letter, postoperative instructions, annotated arthroscopy images, and a personalized video from the surgeon. Patients were called 2 to 5 days after surgery to answer survey questions and recall the 3 words they were told on the day of surgery. Results: Of the 160 patients, 100% received and accessed the e-mail. When asked if they remembered the postoperative conversation, 125 (78.1%) patients responded yes and 35 (21.9%) responded no. When asked to rate how well they remembered the postoperative conversation, 75.2% patients rated their memory very poor (48, 38.4%) or poor (46, 36.8%). Similarly, 129 (80.6%) patients were unable to remember the 3 surgeon-related words. One hundred percent of patients strongly agreed (145, 90.6%) or agreed (15, 9.4%) the e-mail package enhanced their experience. In addition, 100% of patients strongly agreed (150, 93.8%) or agreed (10, 6.2%) the surgeon video enhanced their experience. The average e-mail shares per patient was 2.5, with 158 (98.7%) of patients sharing the e-mail at least once. Conclusions: This study shows that patients had poor memory of in-person conversations on the day of surgery. However, patients were satisfied with a postoperative multimedia package provided via e-mail after surgery. Patients interacted with the e-mail primarily on their cell phones, liked the surgeon video, and shared the e-mail with others. Level of evidence: Level IV, therapeutic case series.